Mediating Effect Of Return On Asset On The Effect Between Internal Capital Disclosure And Stock’s Return - Kohardinata, Cliff; Widianingsih, Luky Patricia; Talahaturusun, Jevan Andreas (Perkumpulan Dosen Muda (PDM) Bengkulu, 2023)
This study aims to examine the effect between internal capital disclosure (ICD) and stock return with the mediation of return on asset (ROA) on the banking sector of Southeast Asia. We find that ICD does not have direct correlation with stock returns, ICD has a positive and significant effect with ROA, ROA has a significant and positive effect with stock return, and the mediating variable ROA can mediate effect between ICD on stock return. Bounded rationality or cognitive limitation resulted in investors needing mediation that ease capturing, memorizing, and processing of information in their minds, one of which is to use return on asset as a bridge between internal capital disclosure and stock return. Aside from that, for investors it is very possible to gain big advantage if they can analyze ICD texts and do trading strategy adjustments, because this study stated that there is a positive effect between ICD and ROA that impacts stock return.